Functional Characterization of the Left Ventrolateral Premotor Cortex in Humans: A Direct Electrophysiological Approach. (5th December 2016) - Fornia, L; Ferpozzi, V; Montagna, M; Rossi, M; Riva, M; Pessina, F; Martinelli Boneschi, F; Borroni, P; Lemon, R N; Bello, L; Cerri, G
Abstract: In monkeys, motor outputs from premotor cortex (PM) involve cortico-cortical connections with primary motor cortex (M1). However, in humans, the functional organization of PM and its relationship with the corticospinal tract (CST) is still uncertain. This study was carried out in 21 patients undergoing intraoperative brain mapping prior to tumor resection. The left ventrolateral premotor cortex (vlPM-BA6) was identified preoperatively by functional magnetic resonance imaging, and then investigated intraoperatively using high frequency direct electrical stimulation (HF-DES) of the convexity of M1 and vlPM-BA6, with simultaneous recording of motor-evoked potentials (MEPs) from oro-facial, hand and arm muscles. The somatotopy, organization of evoked responses, latency of MEPs, and cortical excitability of vlPM-BA6 were compared with reference data from M1. vlPM-BA6 was found to be less excitable, with significantly longer MEP latencies than M1. In addition to the pure oro-facial and hand-arm muscle representation, a "transition oro-hand zone" was identified in vlPM-BA6. The longer latency of vlPM-BA6 MEPs suggests that human vlPM could act on spinal motoneurons either directly through more slowly conducting CST fibers or via less direct pathways through M1, brainstem, or spinal mechanisms. The results help in disclosing the very different roles of vlPM and M1 in motor control.